Life stress and suicidal ideation in Australian men - cross-sectional analysis of the Australian longitudinal study on male health baseline data - Dianne Currier; Matthew J. Spittal; George Patton; Jane Pirkis (BMC, 2016)
Abstract Background Suicide is a leading cause of death in Australian males aged 18 to 55. Non-fatal suicidal behaviours and thoughts are indicators of increased risk for future suicide. Suicidal behaviour is complex and multi-determined. Research supports the involvement of stressful life events in suicide and suicidal behaviour, however the evidence regarding suicidal thoughts is less developed. This study investigates stressful life events in relation to suicidal ideation in a large cohort of adult males recruited into Ten to Men, the Australian Longitudinal Study on Male Health. Methods Baseline data from a national cohort of 13, 884 males aged 18-55 years on suicidal behaviour, psychiatric disorder and life events was used. Multivariable logistic regressions were conducted with current suicidal ideation as the outcome and 12 month life events, 12 month depression, anxiety and harmful/hazardous alcohol use, and socio-demographics as covariates. Further logistic regression models investigated the relative risk of life stress alone, depression/alcohol/anxiety alone and co-occurring life stress and depression/alcohol/anxiety. Results In multivariable models there was an independent contribution to suicidal ideation for six of 24 life events (ORs 1.27-1.95), 12 month depression (OR 4.49) harmful alcohol use (OR 1.38) and anxiety disorders (OR 1.27). Life events co-occurring with depression (OR 10.3) was higher risk than either alone (depression OR 6.6; life stress OR 2.6). There was a lesser effect for co-occurrence in the anxiety and harmful alcohol use models. Conclusion Life events appear to be related to suicidal ideation independent of depression, anxiety and harmful alcohol use in adult males, however if life events occur in the context of depression that risk is substantially increased.